2006
DOI: 10.1016/j.amc.2005.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Two-stage genetic programming (2SGP) for the credit scoring model

Abstract: Credit scoring models have been widely studied in the areas of statistics, machine learning, and artificial intelligence (AI). Many novel approaches such as artificial neural networks (ANNs), rough sets, or decision trees have been proposed to increase the accuracy of credit scoring models. Since an improvement in accuracy of a fraction of a percent might translate into significant savings, a more sophisticated model should be proposed for significantly improving the accuracy of the credit scoring models. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(76 citation statements)
references
References 28 publications
0
71
0
2
Order By: Relevance
“…For example, Ong et al 2005 used genetic programming (GP) for individual credit and concluded that GP is superior to benchmarks such as neural networks, decision trees, rough sets, and logistic regression. Huang et al 2006 proposed two-stage genetic programming (2SGP) to manage individual credit scoring problems by incorporating the advantages of if-then rules and the discriminant function. The author found that 2SGP provides superior accuracy compared to other models.…”
Section: Artificial Intelligence Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Ong et al 2005 used genetic programming (GP) for individual credit and concluded that GP is superior to benchmarks such as neural networks, decision trees, rough sets, and logistic regression. Huang et al 2006 proposed two-stage genetic programming (2SGP) to manage individual credit scoring problems by incorporating the advantages of if-then rules and the discriminant function. The author found that 2SGP provides superior accuracy compared to other models.…”
Section: Artificial Intelligence Methodsmentioning
confidence: 99%
“…Particularly, when investing in government debt or loans, country (or government) credit should be considered a primary risk factor, namely, country risk represents the debt paying capability of the government. Similarly, when trading in commodity markets and investing in financial markets, the ability of the target corporations or individuals to meet debt obligations should be carefully estimated by credit scoring or rating using information about history records, current economic state, and other attributes (Huang et al 2004;Huang et al 2006). For example, commercial banks make financial loan decisions and issue credit cards to customers dependent on corporate (or individual) credit ratings or credit scores.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, GP is more flexible in symbolic setting than conventional regression method or data-mining approach (e.g., ANN). Notably, GP is also widely utilized in practical applications such as in forecasting [10][11][12]42] and classification [8,43].…”
Section: Genetic Programmingmentioning
confidence: 99%
“…When selecting input variables, GP automatically finds variables that contribute most to the model [11,42] and does not have any restriction for data size, as compared to an ANN or large data-set [8,43]. …”
Section: Genetic Programmingmentioning
confidence: 99%
“…A neural network is a system made of highly interconnected and interacting processing units that are based on neurobiological models mimicking the way the nervous system works. It usually consists of a three layered system comprising input, hidden, and output layers [1,4,5,33] . A Cascade Correlation Neural Network (CCNN) is a special type of neural network used for classification purposes.…”
Section: Related Studiesmentioning
confidence: 99%